Patients’ Health Beliefs and Practices and Compliance with Discharge Instructions - Palompon, Daisy R. (JPAIR Multidisciplinary Research, 2009)
This study was purposely designed to determine the level of influence between health beliefs and practices and level of compliance with discharge instructions by the patients in selected hospitals in Sogod, Southern Leyte. Utilizing a quantitative qualitative and correlational design, thirty respondents were selected by purposive sampling technique with the following inclusion criteria: previously hospitalized with a minimum of three days and discharged within the year, 15 to 70 years old and with medical problems. A researcher-made interview schedule was utilized with two parts such as seven questions relating to patient’s personal data and eight questions pertaining to the problem. Variables on compliance with discharge instructions and out-patient referrals were categorized into high, moderate and poor compliance. Respondents’ health beliefs and practices were also classified as traditional, parochial and scientific. Data were analyzed using percentage and chi-square in which the level of significance was set at 0.05. Based on the findings, it is concluded that health beliefs and practices do not influence compliance of medication since it is basically a consideration of individual’s budgetary capacity. It is further concluded that health beliefs and practices significantly influence outpatient referral compliance since it is basically affected more on behavioral attributes rather than economic implications.